Method for calculating the kilovolt-ampere rating of a 24-pulse autotransformer-rectifier unit - Roginskaya Lyubov; Gorbunov Anton; Karimov Ruslan; Bakirov Ayaz; Shiryaev Oleg; Yanuzakova Violetta (E3S Web of Conferences)
The article analyzes the operation of a direct current power source based on a 24-pulse autotransformer-rectifier unit using electrically connected secondary windings located on different rods, as well as a winding connected in a delta. Electromagnetic processes in the proposed converter are investigated with obtaining theoretical curves of currents and magnetomotive forces of the windings. Calculation of effective values in relative units of currents and magnetomotive forces of the windings of the autotransformer-rectifier unit is made based on the analysis of the obtained curves. A method for analytical calculation of the kilovolt-ampere rating of the proposed three-phase-twelve-phase autotransformer converter of the number of phases for a 24-pulse rectifier is developed. The results of calculating the kilovolt-ampere rating of the autotransformer converter are obtained taking into account the secondary windings with taps and the winding connected in a delta. The method and the result of calculating the distribution coefficient for a three-phase-twelve-phase converter, taking into account the phase shift of the secondary system voltages, are shown for a more accurate calculation of the primary power of the device. It is revealed that the proposed converter circuit provides a decrease in kilovolt-ampere rating, compared to known devices based on 24-pulse transformer-rectifier units.